Electrochemical removal of diazinon insecticide in aqueous solution by Pb/β-PbO2 anode. Effect of parameters and optimization using response surface methodology - Mahmoudpoor Moteshaker, Parisa (Water environment research : a research publication of the Water Environment Federation, 2020)
© 2019 Water Environment Federation.